Gastrointestinal Tract Findings in Patients with Primary Immunodeficiency: A Single-Center 6-Year Experience - Erkoç, Merve Merve; Erhan, Çiğdem; Çevirme, Leyla; Basır, Hakan; Dik, Susamber; Cansunar, Reyhan Sevil; Özden, Güzin (Turkish Journal of Gastroenterology, 2025)
Background/Aims: The aim was to determine the findings of the gastrointestinal system, which is the second most frequently affected system in the primary immunodeficiency (PID) patient population, and the frequency of these findings. Materials and Methods: Fifty patients with PID were included in this study, and the characteristics of the patients, upper gastrointesti nal endoscopy, colonoscopy, and biopsy (endoscopic and colonoscopic) results were evaluated. Results: The median age of patients included in the study was 31 years (range 18-72 years) and 64% were male. Seventy-two percentnof the patients had common variable immunodeficiency (CVID) and 68% were diagnosed in adulthood. Chronic diarrhea was present in 48% of the patients, and body mass index was lower in this group. Switched memory B cells were lower in chronic diarrhea (P = .003). Twenty-nine patients underwent upper gastrointestinal endoscopy, and the most common macroscopic findings were gastropathy (79.3%), duodenopathy (37.9%), and esophagitis (27.6%). Of the 23 patients who underwent colonoscopy, 14 had at least 1 macro scopic finding other than internal hemorrhoids and only 1 patient had no macroscopic findings. One patient had mucosa-associated lymphoid tissue lymphoma (MALToma) on gastric biopsy, while 1 patient had poorly differentiated adenocarcinoma on antrum biopsy. Conclusion: In conclusion, chronic diarrhea is more common in PID than in the general population, and switched memory B cells arenlower in PID patients with chronic diarrhea. Most importantly, a collaboration between immunologists, gastroenterologists, and patholo gists is required when evaluating the gastrointestinal tract in PID. Cite this article as: Erkoç M, Erhan Ç, Çevirme L, et al. Gastrointestinal tract findings in patients with primary immunodeficiency: A single-center 6-year experience. Turk J Gastroenterol. Published online August 25, 2025. doi 10.5152/tjg.2025.25100.